Evaluation of oral care using MA-T gel for high-risk patients: a pilot study - Hitomi Ono-Minagi; Nao Gojo; Tsutomu Nohno; Tsuyoshi Inoue; Hideyo Ohuchi; Takayoshi Sakai (BMC, 2023)
Abstract Background Oral care with gel is a common method for preventing aspiration in high-risk patients. An oral care gel is used to clean and moisturize the oral cavity. However, the effects of gel care on the oral bacteria remain unclear. In this pilot study, we described a matching transformation system (MA-T) for elderly high-risk patients. MA-T is an on-demand aqueous chlorine dioxide solution that provides excellent safety and has various antimicrobial activities, even in the presence of abundant organic compounds. This study investigated the effects of MA-T gel in patients requiring nursing care. Materials and methods Patients who were hospitalized for nursing care were included in this study. No drugs and foods were administered orally. Oral bacteria and intraoral humidity were examined by daily care using MA-T gel. Moreover, oral membranous substances were analyzed and material from the oral cavity was cultured on selective media for identifying opportunistic organisms. Results Membranous substances were present in the oral cavities of all patients. The number of bacteria decreased, and oral moisture improved, after treatment with MA-T gel. Moreover, oral humidity was also controlled with the continued use of MA-T gel. MA-T gels should be used not only for professional care but also on a daily basis for better oral care. Furthermore, the results of bacterial cultures showed that MA-T controls the propagation of opportunistic bacterial infections. Conclusion Membranous substances may be observed in the oral cavity of individuals requiring nursing care for tube feeding. The results of this pilot study suggest that MA-T, a novel disinfectant, can be used for oral care in the elderly to reduce the risk of aspiration-pneumonia.